Exercise intensity and physical fitness modulate lipoproteins profile during acute aerobic exercise session - Antunes, B. M. (Sci Rep, 2020)
Physical inactivity has emerged as an important cardiometabolic risk factor; however, the beneficial impacts of physical exercise according physical fitness status are still unclear. To analyze the lipoproteins and immune-endocrine response to acute aerobic exercise sessions performed at different intensities according physical fitness status and evaluated the gene expression in monocyte cells. Twelve individuals, divided into Low and High VO(2max,) performed three randomized acute exercise sessions at low (<60% VO(2max)), moderate (60–75% VO(2max)), and high (>90% VO(2max)) intensities. Blood samples were collected pre, immediately post, and 60 minutes post-exercise to analyze NEFA, triacylglycerol, non-HDL-c, HDL-c, PAI-1, leptin and adiponectin concentrations. Blood samples were collected from another set of twelve individuals for use in monocyte cell cultures to analyze L-CAT, CETP, and AMPK gene expressions. Low VO(2max) group pre-exercise exhibited higher postprandial leptin and total cholesterol concentrations than High VO(2max) group (p < 0.05). Exercise performed in high-intensity promoted a decreased leptin and NEFA levels (p < 0.05, for both), but for PAI-1 levels was decreased (p < 0.05) only for the Low VO(2max) group. Triacylglycerol levels decreased after all exercise sessions (p < 0.05) for both groups, and HDL-c exhibited decrease during moderate-intensity (p < 0.05), but this scenario was attenuated in Low VO(2max) group. Low VO(2max) individuals exhibit some metabolic-endocrine disruption, and acute aerobic exercise sessions performed at low, moderate, and high intensities are capable of modulating metabolic-endocrine parameters, mainly at high-intensity, in a physical fitness-dependent way, given that Low VO(2max) group was more responsive and seem to be able to appropriate more exercise-related benefits.